The sociolinguistics of place and belonging perspectives from the margins - Cornips, Leonie Elise Alexandra; Rooij, Vincent A. de (Impact, studies in language and society ;, 2018)
This volume shows the relevance of the concepts of `place' and `belonging' for understanding the dynamics of identification through language. It also opens up a new terrain for sociolinguistic and linguistic anthropological study, namely the margins. Rural, as well as urbanized areas that are seen as marginal or peripheral to places that are overtly recognized as mixed and hybridized have received relatively little sociolinguistic attention. Yet, people living in these supposedly less `spectacular' margins are not immune to the effects of globalization and rapid technological change. They too constantly form new ensembles from linguistic and cultural resources which they invest with novel, instable, often ambiguous meanings. This volume focusses on the purportedly unspectacular in order to achieve a full understanding of the relation between language, place and belonging. The contributors to this volume, therefore, focus on language practices analyzing them as dialectically related to political-economic processes and language ideologies.